If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(1 + -7v) = -456 (1 * -8 + -7v * -8) = -456 (-8 + 56v) = -456 Solving -8 + 56v = -456 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 56v = -456 + 8 Combine like terms: -8 + 8 = 0 0 + 56v = -456 + 8 56v = -456 + 8 Combine like terms: -456 + 8 = -448 56v = -448 Divide each side by '56'. v = -8 Simplifying v = -8
| 5a-2+6a= | | 6x-1/2=36 | | (4x+3)+(4x+3)+(3x-2)=6x | | 800=60x+2x^2 | | 7-5x=5x-6x+7 | | 8x+2(-4-5x)=-12 | | -3x=-2/3x-5/9 | | 5r-25=-5(5-6r) | | 1/2x=16=36 | | 8/5=32-× | | .2(4z+6)=36 | | 3b+7-2-5b= | | v^2+22v+121=24 | | 9x+5+2=7 | | 6x+20+(-5)-3x=2x-35 | | 0.7x=0.6(30-x) | | 10n-12n-8n=-4+16 | | 4x+21x-6= | | 7=-2-y | | 5b-10=45b-45 | | -(4x+3)-3= | | 2r-8=-12 | | (2b+1)-b=-4 | | 8+3n-7=8n+6-6n | | 5(b-2)=15(3b-3) | | 6x*7y=-9 | | -7=-2+k | | 7+8=5+2 | | 5b-10=45b+45 | | 3(x-1)-x=-2x+3(x-1) | | (4x-2)+(2x+14)=5x+10 | | 5h-(1.5h+4)=10 |